Influence of drug loading on the physical stability of phospholipid-stabilised colloidal lipid emulsions - Nadine Monika Francke; Heike Bunjes (Elsevier, 2020)
When poorly water-soluble drugs are formulated in colloidal lipid emulsions, adequate stability of the emulsion must be ensured. The aim of this work was to investigate different aspects related to drug loading in order to gain a better understanding on how drugs affect the stability of phospholipid-stabilised emulsions. To obtain information on emulsion stability, a rapid and reproduceable shaking test was developed. A passive loading approach was applied for drug loading of the commercially available nanoemulsion Lipofundin® MCT/LCT 10% with seven drugs of different charge and localisation tendency within the emulsion system. Localisation of drug molecules in the droplet interface did not generally lead to destabilisation of the emulsion, whereas the charge of the drug was of decisive importance. Aspects such as the drug concentration, its influence on the pH and the impact of zeta potential changes had an influence on emulsion stability as well. Certain destabilising effects of drugs could be counteracted by modification of the pH. Lipofundin® MCT/LCT 10%, passively loaded with propofol, was compared with two commercially available propofol preparations. No negative effect of the passive loading procedure could be detected.